EU-MERCOSUR Trade Agreement : Potential Impacts on Rural Livelihoods and Gender (with Focus on Bio-fuels Feedstock Expansion) /: Potential Impacts on Rural Livelihoods and Gender (with Focus on Bio-fuels Feedstock Expansion). ([February 2008?]) - Hinojosa, Leonith
No abstract available